The complete chloroplast genome of Anoectochilus roxburghii. (1st November 2016) - Zeng, Xu; Liu, Mengmeng; Li, Yuanyuan; Meng, Zhixia; Guo, Shunxing
Abstract: We determined the complete chloroplast (cp) genome of Anoectochilus roxburghii, a well-known medicinal orchid. The total genome size was 156, 252 bp in length, containing a pair of inverted repeats (IRs) of 26, 591 bp, a large single copy (LSC) of 84, 665 bp and a small single copy (SSC) of 18, 405 bp. The overall GC content of the genome was 37.71%. The cp genome of A. roxburghii contained 87 protein-coding genes, 38 tRNA genes, and eight rRNA genes. Of these 18 genes, one or two contained introns. A maximum parsimony phylogenetic tree revealed that the cp genome of A. roxburghii was closely related to that of the orchid within the Orchidoideae subfamily.